Policies, Enforcement, and Customs Evasion : Evidence from India - Mishra, Prachi (IMF Working Papers; Working Paper ;, 2007)
We examine the effect of tariff policies on evasion of customs duties, in the context of the trade reform in India of the 1990s. We exploit the variation in tariff rates across time and products to identify the evasion elasticity, namely, the effect of tariffs on evasion, and relate this elasticity to factors related to customs enforcement or the quality of customs institutions. We find a positive and robust effect of tariffs on import tax evasion. We then show that the evasion elasticity is influenced by certain product characteristics that determine how easy it is to detect evasion (with more differentiated products exhibiting a higher evasion elasticity). This evasion elasticity, which we broadly interpret as reflecting the quality of customs administration, has not improved over the 1990s. Finally, our results suggest that the effectiveness of customs in addressing evasion may be better in India than China, although China appears to be catching up over time.